Statistical Optimization Amalgamated Approach on Formulation Development of Nano Lipid Carrier Loaded Hydrophilic Gel of Fluticasone Propionate - Chandrashekar, Harshitha; Bhattacharyya, Sayani (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Formulation of a nano lipid carrier loaded hydrophilic gel of a corticosteroid, fluticasone propionate (FP) was investigated systemically with response surface model (RSM) for promising dermal delivery of the drug. Objectives: To achieve a better penetration of the drug and to overcome the generally associated adverse reactions of corticosteroids, the present study, explored the formulation and evaluation of nano lipid carriers (NLCs) of FP in a hydrophilic gel base. Methods: A central composite design was proposed to study the effect of processing materials on the physicochemical properties of the NLC. High shear homogenization method with stearic acid, isopropyl myristate and poloxamer 407 was used to make different batches of FP-NLCs. The model was optimized at a significance level of P<0.05. FTIR, DSC and surface morphology studies were carried out for the optimized product. The optimized product was incorporated in the Carbopol P940 gel base and was evaluated for its mechanical and rheological properties, ex-vivo permeation and skin irritation study. Results: It was observed that using the proposed model, a nano size (179 nm) stable (Zeta potential -26 mV) optimized product of FP-NLC with 85% entrapment efficiency was achieved. The nanogel exhibited a spreadability of 4.2 gm.cm/sec and a viscosity of 92.6 cp. Approximately 3.5 times improvement in ex-vivo permeation and no skin irritations on animals were reported on application of the nanogel of FP. Conclusion: Hence the investigation created a paradigm to explore the efficacy of nanogel of FP for dermal application with improved permeation and promising therapy for dermatitis.
Keywords: Fluticasone propionate; Niosome; Central composite design; Gel; Ex-vivo; permeation